Empowerment of Supervisors for Achieving Madrasah Innovation: A Case Study at Mts Laboratory in Jambi City - Athiatul Haqqi; Maisah Maisah; Fadlilah Fadlilah (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to explore and analyze the empowerment of supervisors in supporting the achievement of innovation at MTS Laboratorium Kota Jambi. Educational supervisors have a central role in encouraging change and innovation in madrasahs. Supervisors are no longer expected to focus only on administrative functions; they are now expected to be able to act as agents of change by guiding principals and teachers in implementing innovative programs. Through the qualitative descriptive case study method, this study is expected to provide a comprehensive understanding of the empowerment of supervisors to achieve innovation at MTS Laboratorium Kota Jambi. The results of the study will provide strategic recommendations for the development of a more adaptive and innovative educational supervision system in madrasahs.